(untitled) (Revista Internacional de Formação de Professores, 2018)
This text is about teachers training through a philosophical bias. From two concepts, “the self-care” and “the three ecologies”, created by the contemporary’s philosophers Michel Foucault and Félix Guatari, it was possible to make approaches and rethink some teacher’s training who seek, in a philosophical practice, alternatives to face changes in their own daily lives and in the school. The training planed is different from the traditional one, but it is close to a continuous process of problematizationof a teacher’s practice concerned with issues which involve life, daily life, contemporaneity, giving attention to relations among people, with the world and the self. This training occurs due to an ethic-political-esthetics process, characteristic of philosophical concepts here dealt. To develop writing, were used as theoretical background of the Philosophies of Difference.